Linear Stability Analysis of the Cahn–Hilliard Equation in Spinodal Region. (24th June 2022) - Ham, Seokjun; Jeong, Darae; Kim, Hyundong; Lee, Chaeyoung; Kwak, Soobin; Hwang, Youngjin; Kim, Junseok
Abstract : We study a linear stability analysis for the Cahn–Hilliard (CH) equation at critical and off-critical compositions. The CH equation is solved by the linearly stabilized splitting scheme and the Fourier-spectral method. We define the analytic and numerical growth rates and compare these growth rates with respect to the different average levels. In this study, the linear stability analysis is conducted by classifying three average levels such as zero average, spinodal average, and near critical point levels of free energy function, in the one-dimensional (1D) space. The numerical results provide insight for the dynamics of CH equation at critical and off-critical compositions.